Positive Social Interaction Offsets Impact of Low Socioeconomic Status on Stress - Woodward, Eva N. (J Natl Med Assoc, 2017)
BACKGROUND: Stress is associated with unhealthy behaviors and premature morbidity and mortality, especially among those of low socioeconomic status (SES). Clarifying the roles of stress-related risk and protective factors can guide interventions designed to reduce stress and improve health among socioeconomically disadvantaged populations. PURPOSE: (1) Replicate prior research showing that lower SES is associated with higher stress in a predominantly racial minority, socioeconomically disadvantaged sample, and (2) test the hypothesis that different types of social support (a protective factor) mitigate the deleterious effects of SES on self-reported perceived stress. METHODS: Low-income patients (N = 508, 54% male, 68% Black, M(age) = 28) from a publicly-funded clinic completed self-report measures as part of a larger trial. Structural equation modeling tested the hypothesized associations among SES, social support, and stress. RESULTS: Individuals of lower SES, β = −0.27 (0.08), p < .01, and lower overall social support, β = −0.47 (0.05), p < .001, reported higher stress. Social support moderated associations between SES and stress, with participants with lower SES benefitting the most from social support. Positive social interaction was the strongest moderator, β = 0.20 (0.08), p = .01. CONCLUSIONS: The associations among SES, stress, and social support corroborate prior research. One specific type of social support (viz., positive social interaction) was particularly important for decreasing stress among socioeconomically disadvantaged persons. Future research to confirm the associations among these factors is needed to inform theory and intervention design.